Formulasi tablet kitosan cangkang kepiting bakau (Scylla serrata) dari co-processed excipient dengan PEG 4000 sebagai meltable binder - Imtihani, Hilya Nur; Natarani, Mutia; Sandy, Yessy Kurnia (Health Sciences and Pharmacy Journal, 2022)
Chitosan has many functions in the health sector, one of which can be used as an anti cholesterol supplement. Co-processing is a technique carried out to obtain new additives by combining two or more existing additives, where the combinations of these materials will complement each other, so that new additives with better (superior) properties are obtained. The purpose of this study was to determine the formulation and evaluation of mud crab shell (Scylla serrata) chitosan tablets from co-processed excipients with PEG 4000 as a meltable binder with a ratio of 10% (F1) and 20% (F2). Co-processed excipients are made using the melt granulation method with additional ingredients, namely lactose as a filler and primogel as a disintegrant. Tablets were printed using the direct compression method with the addition of Mg Stearate as a lubricant. The results of the co-processed excipient evaluation showed that each granule met the requirements for the flow rate test, angle of repose test, compressibility test and Hausner's ratio. From the results of statistical tests using the Mann-whitney test method, there is a significant difference between co-processed excipient PEG 4000 10% and PEG 4000 20% as a meltable binder for the parameters of water content with F2 moisture content (1.67%) lower than in F1 (3.33%). In the evaluation of chitosan tablets, they produced tablets that met the test requirements for weight uniformity, tablet friability (F1), tablet hardness, disintegration time (F2) and did not meet the requirements for the tablet size uniformity test. The selected formula for this study was F2 with a PEG 4000 meltable binder of 20% because it produced tablets that met disintegration time with low water content.